A cost‐effectiveness analysis of Erwinia asparaginase therapy in children with acute lymphoblastic leukemia. Issue 1 (23rd September 2018) - Kloos, Robin Q. H.; van Litsenburg, Raphaële R. L.; Wolf, Sarah; Wismans, Leonoor; Kaspers, Gertjan J. L.; Uyl‐de Groot, Carin A.; Pieters, Rob; van der Sluis, Inge M.
Abstract: Objectives: Erwinia asparaginase is used as a second‐line formulation after a neutralizing hypersensitivity reaction to the first‐line formulation of asparaginase. Here, we have performed a cost‐effectiveness analysis of Erwinia asparaginase treatment. Methods: Children with acute lymphoblastic leukemia treated according to the Dutch Childhood Oncology ALL‐10 or ALL‐11 protocol were included and initially treated with PEGasparaginase in the intensification phase. The total treatment costs of this treatment phase, quality of life (QoL), and life years saved (LYS) were studied for two scenarios: (a) patients were switched to Erwinia asparaginase treatment after a hypersensitivity reaction, or (b) asparaginase would have been permanently stopped. Results: Sixty‐eight patients were included. There was no difference in QoL between patients with and without a hypersensitivity reaction. The mean costs of the intensification phase per patient were 40, 925 if PEGasparaginase could be continued, 175, 632 if patients had to switch to Erwinia asparaginase, and 21, 190 if asparaginase would have been permanently stopped. An extrapolation of the literature suggests that the 5‐year event‐free survival would be 10.3% lower without intensive asparaginase treatment if asparaginase is stopped after a reaction. Thus, the costs per LYS were 1892 for scenario 1 and 872 for scenario 2. Conclusions: Switching to Erwinia asparaginase increases the costs per LYS by 1020, which is modest in view of the total costs. Moreover, when asparaginase treatment can be completed by switching to Erwinia asparaginase, relapses—and consequential costs—will be avoided. Therefore, from a cost perspective, we recommend a switch to Erwinia asparaginase to complete asparaginase treatment.